Pencegahan Stunting Melalui Penguatan Peran Kader Gizi dan Ibu Hamil Serta Ibu Menyusui Melalui Participatory Hygiene and Sanitation Transformation (PHAST) - Khoiron Khoiron; Dewi Rokhmah; Nur Astuti; Globila Nurika; Dewa Putra (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
Stunting is a chronic nutritional problem caused by lack of nutrition for a long time. Sumberwringin Village is one of the villages in Bondowoso Regency with a fairly high number of cases of stunting under five and is one of the fostered villages of the University of Jember that requires assistance in resolving public health problems, especially regarding the handling of nutrition and stunting problems. Food and nutrition insights from community program actors, such as nutrition cadres, pregnant women, and breastfeeding mothers play an important role in efforts to prevent and improve stunting problems in Indonesia.The aim of the implementation of this community service activity is to increase the competence (cognitive, affective, and psychomotor) of posyandu cadres in providing education to the community about stunting prevention based on community participation through changes in personal hygiene and sanitation, and preventing pregnant women and breastfeeding mothers gave birth to a stunting baby. The subjects of the training activities were 34 pregnant women and mothers under five in Sumberwringin Village, Sumberwringin District, Bondowoso Regency. This activity was carried out by means of lectures and discussion questions and answers regarding the material of Stunting Prevention with the PHAST Method. The results of this activity indicated that there was a significant difference in the level of knowledge among all participants before and after being given material related to stunting and environmental health with an average increase of 30 points. This activity can be concluded that community service activities in preventing stunting through Participatory Hygiene and Sanitation Transformation (PHAST) are able to increase participants' knowledge about Stunting Prevention with the PHAST Method.